PENGARUH FINANCIAL DISTRESS DAN PROFITABILITAS TERHADAP MANAJEMEN LABA DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI: (Studi Empiris Pada Perusahaan Sektor Bahan Dasar Yang Terdaftar Di BEI Periode Tahun 2021-2023) - Aulia, Nazarina; Setiyono, Taufiq Andre (Perwira Journal of Economics & Business, 2025)
This study aims to examine the effect of financial distress and profitability on earnings management with audit quality as a moderating variable in basic materials sector companies listed on the Indonesia Stock Exchange (IDX). The population of this study consists of 103 basic materials sector companies. Out of 103 companies, only 38 companies met the criteria. The observation period for this study spans 3 years, from 2021 to 2023, resulting in a final data of 114 companies. Sampling was conducted using the purposive sampling technique. The study employs Moderated Regression Analysis (MRA) processed through the IBM SPSS 27 application. The results show that, partially, financial distress has a significant negative effect on earnings management, profitability has a significant positive effect on earnings management, audit quality strengthens the effect of financial distress on earnings management, and audit quality does not moderate the effect of profitability on earnings management. Investors and creditors should be more cautious in allocating and lending their funds. They should also consider audit quality in their decision-making process.